Environmental health case studies at Kampung Masjid, Mukim 9, Teluk Kumbar, Pulau Pinang / Siti Nur Sakinah Abd. Rani - Abd.Rani, Siti Nur Sakinah (2016)
This study is about the improper drainage system at Kampung Masjid, Teluk Kumbar. The effectiveness of drainage system plays vital roles to protect and maintain our health and environment. This study involve the villagers who live in Kampung Masjid. The design of this study is cross-sectional study where it involved 100 respondents which are 68 females and 32 males. This study use probability sampling which is stratifed sampling. The data was collected by using different methods like sample selection, oral interview, secondary data and data analysis.The instrument that used in this study is questionnaire that provided by UiTM. The respondents must answer all the question that have asked. The questionnaire have six parts all together.Their answers are completely confidential and are safely used for the purpose of my study. All the data will be analysis in the Microsoft Excel and it will be presented in the form of bar chart, pie chart, table and line graph. The purpose of my study is to identify the causes, effects and also some recommendation to improve the drainage system for preventing more health problem arise in future. The main causes of drainage system blocked are poor maintenance, illegal dumping in the drains, and the process of development in the study area. Therefore, the effects of poorly drains are always occur flash flood, become source of spreading vector-borne diseases and also give physical and economic impacts to villagers. Thus, all the villagers shall be more responsible to ensure that the drainage system is functional effectively with water flowing smoothly for prevent all the effects in future.